Effectiveness of Outreach and Assistance on the Quality of Female Sex Workers' Reproductive Health Care - Hitijahubessy, Christy Natalia Magdalena (Journal of Midwifery and Nursing, 2024)
Female sex workers (FSWs) are women who rent themselves out for the enjoyment of others and expect a reward or wage. PSPs are women who work daily by selling or renting their bodies, either directly, indirectly or freelance. This work certainly has an impact on their reproductive health, because this profession involves risky sexual activities. Risky sexual activity is any sexual activity that has a negative impact, such as unwanted pregnancy, abortion and sexually transmitted infections. The purpose of this study is to conduct outreach and assistance for FSWs to prevent sexually transmitted infections. The research method used design with a cross-sectional approach. Subjects in the Rainbow Foundation of Maluku Ambon assisted community. The results of this study show that outreach and assistance programs are very effective in efforts to prevent sexually transmitted infections among female sex workers.